Mini-review: air-assisted spray nozzles and applications - Zhao, Yuanfeng; Huang, Yunlong; He, Zhixia; Zhong, Wenjun (Frontiers in Physics, 2025)
This mini-review summarizes the fundamental principle, spray phenomena, and atomization mechanism of air-assisted spray nozzles, and applications in various aerospace propulsion systems, agriculture irrigation, and some promising areas. The structural configurations and atomization mechanisms of air-assisted nozzles are first introduced, followed by an analysis of key design parameters and their influence on atomization performance. The air-assisted atomization process is further characterized through typical flow regimes, vortex identification techniques, and integrated experimental–numerical approaches. Current practical applications are reviewed, along with potential optimization strategies for nozzle design. Future development directions should emphasize integration with smart agriculture technologies to address emerging demands and challenges in agricultural irrigation and atomization systems.